2020
DOI: 10.1038/s41419-020-2404-5
|View full text |Cite
|
Sign up to set email alerts
|

Elevated intracellular copper contributes a unique role to kidney fibrosis by lysyl oxidase mediated matrix crosslinking

Abstract: Copper ions play various roles in mammalian cells, presumably due to their involvement in different enzymatic reactions. Some studies indicated that serum copper correlates with fibrosis in organs, such as liver and lung. However, the mechanism is unknown. Here, we explored the role of copper in kidney fibrosis development and possible underlying mechanisms. We found that copper transporter 1 (CTR1) expression was increased in the kidney tissues in two fibrosis models and in patients with kidney fibrosis. Simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 45 publications
(46 reference statements)
9
42
0
Order By: Relevance
“…Circulating copper is somewhat genetically controlled [1], but humans are also exposed to copper through dietary intake and it reaches the kidney through blood circulation [18]. In the kidneys, copper catalyzes the production of highly reactive hydroxyl radical species, so this oxidative stress can cause proximal tube necrosis [5,18]. Previously, through observational epidemiological studies, it has been reported that higher copper intake has been associated with abnormal eGFR [16] and end stage CKD [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating copper is somewhat genetically controlled [1], but humans are also exposed to copper through dietary intake and it reaches the kidney through blood circulation [18]. In the kidneys, copper catalyzes the production of highly reactive hydroxyl radical species, so this oxidative stress can cause proximal tube necrosis [5,18]. Previously, through observational epidemiological studies, it has been reported that higher copper intake has been associated with abnormal eGFR [16] and end stage CKD [19].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive dietary copper intake can lead to deposition of copper in the kidney and cause nephrotoxicity characterized by proximal tube necrosis that results through oxidative stress, cellular injury, and leads to a decline in kidney function [4]. However, the interplay between copper and kidney disease is bi-directional as imbalances in the homeostasis of circulating copper levels may also occur as a result of impaired renal excretion and changes in protein metabolism in patients with chronic kidney disease (CKD) [5]. In fact, the regulation of copper levels in CKD patients is important to prevent complications.…”
Section: Introductionmentioning
confidence: 99%
“…22,38 In addition to the liver, LOXL1 has also been shown to exert a fibrotic effect in lungs 39 and kidneys. 40 Indeed, the roles of LOX and LOXL2 in fibrosis have been well characterized, and their inhibition has yielded promising results in mouse experiments. 7,15,31,41 Therefore, the LOX family is a logical target for antifibrotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has recently been demonstrated that intracellular copper accumulation is associated with kidney fibrosis and function. 30 The present case demonstrates that the search for a proper aetiology of interstitial nephritis remains challenging.…”
Section: Discussionmentioning
confidence: 85%
“…As copper ions play an important role in enzymatic processes in cells, changes in copper levels could have cellular effects. Indeed, it has recently been demonstrated that intracellular copper accumulation is associated with kidney fibrosis and function 30 …”
Section: Discussionmentioning
confidence: 99%